Economic modeling of risk-adapted screen-and-treat strategies in women at high risk for breast or ovarian cancer - Müller, Karsten; Danner, Marion; Schmutzler, Rita; Engel, Christoph; Wassermann, Kirsten; Stollenwerk, Björn; Stock, Stephanie; Rhiem, Kerstin (The European journal of health economics : HEPAC : health economics in prevention and care, 2019)
BACKGROUND The ’German Consortium for Hereditary Breast and Ovarian Cancer’ (GC-HBOC) offers women with a family history of breast and ovarian cancer genetic counseling. The aim of this modeling study was to evaluate the cost-effectiveness of genetic testing for BRCA 1/2 in women with a high familial risk followed by different preventive interventions (intensified surveillance, risk-reducing bilateral mastectomy, risk-reducing bilateral salpingo-oophorectomy, or both mastectomy and salpingo-oophorectomy) compared to no genetic test. METHODS A Markov model with a lifelong time horizon was developed for a cohort of 35-year-old women with a BRCA 1/2 mutation probability of ≥ 10%. The perspective of the German statutory health insurance (SHI) was adopted. The model included the health states ’well’ (women with increased risk), ’breast cancer without metastases’, ’breast cancer with metastases’, ’ovarian cancer’, ’death’, and two post (non-metastatic) breast or ovarian cancer states. Outcomes were costs, quality of life years gained (QALYs) and life years gained (LYG). Important data used for the model were obtained from 4380 women enrolled in the GC-HBOC. RESULTS Compared with the no test strategy, genetic testing with subsequent surgical and non-surgical treatment options provided to women with deleterious BRCA 1 or 2 mutations resulted in additional costs of \text€7256 and additional QALYs of 0,43 (incremental cost-effectiveness ratio of \text€17,027 per QALY; cost per LYG: \text€22,318). The results were robust in deterministic and probabilistic sensitivity analyses. CONCLUSION The provision of genetic testing to high-risk women with a BRCA1 and two mutation probability of ≥ 10% based on the individual family cancer history appears to be a cost-effective option for the SHI.